Carotenoid biosynthetic gene expression, pigment and n-3 fatty acid contents in carotenoid-rich Tetraselmis striata CTP4 strains under heat stress combined with high light - Schüler, Lisa Maylin (2021)
In this study, two carotenoid-rich strains of the euryhaline microalga Tetraselmis striata CTP4 were isolated by random mutagenesis combined with selection via fluorescence activated cell sorting and growth on norflurazon. Both strains, ED5 and B11, showed an up to 1.5-fold increase in carotenoid contents as compared with the wildtype, independent of the growth conditions. More specifically, violaxanthin, beta-carotene and lutein contents reached as high as 1.63, 4.20 and 3.81 mg g-1 DW, respectively. Genes coding for phytoene synthase, phytoene desaturase, lycopene-beta-cyclase and epsilon-ring hydroxylase involved in carotenoid biosynthesis were found to be upregulated in ED5 and B11 cells as compared to the wildtype. Both strains showed higher contents of eicosapentaenoic acid as compared with those of the wildtype, reaching up to 4.41 and 2.88 mg g-1 DW, respectively. Overall, these results highlight the complexity of changes in carotenoid biosynthesis regulation that are required to improve pigment contents in microalgae.